FINANCIAL DEEPENING DAN KEMISKINAN DI INDONESIA - Hella Citra; Raja Masbar; sofyan Syahnur (Syiah Kuala University, 2018)
AbstractThis study aims to analyze the effect of macro variables in the form of real GDP, exchange rate,inflation and deposit rates against Financial Deepeningin Indonesia, as well as to analyze the effect of FinancialDeepening on poverty alleviation in Indonesia. Thisstudy uses time series data from 2000 to 2017. The modelused is Multiple Linear Regression Analysis and SimpleRegression Analysis using Microsoft Excel 2003software, Herodes 1.4, SPSS 24, and Eviews 8. Theresults show that with the level of confidence 95 percent,real GDP, exchange rate and interest rate have positiveeffect on Financial Deepening, while inflation does notaffect Financial Deepening. Furthermore, FinancialDeepening has a negative effect on the number of poorpeople. The government should make more efforts instabilizing Indonesia's macroeconomic conditionsthrough appropriate policies to keep the value of moneystable. It is suggested for further research to add otherfinancial deepening indicators such as credit ratio ordeposit ratio so that it can be done comparison ofanalysis, and can include other independent variablesuch as investment. In addition it can also examine thestate of financial deepening other countries to becomparable to the state of Indonesia, and using othermethods.